2020
DOI: 10.1186/s13046-020-01702-y
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin promotes EMT in pancreatic cancer via mediating Ca2+ dependent acute and chronic endoplasmic reticulum stress

Abstract: Background Our previous study showed that calreticulin (CRT) promoted EGF-induced epithelial-mesenchymal transition (EMT) in pancreatic cancer (PC) via Integrin/EGFR-ERK/MAPK signaling. We next investigated the novel signal pathway and molecular mechanism involving the oncogenic role of CRT in PC. Methods We investigated the potential role and mechanism of CRT in regulating intracellular free Ca2+ dependent acute and chronic endoplas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 78 publications
(89 reference statements)
3
24
0
Order By: Relevance
“…4 B and C). Given recent studies showing that CALR promotes epithelial-mesenchymal transition in PDAC [ 28 , 29 ], our results indicate that CALR and ITGA3 could be one of the pathways through which CAFs send the epithelial-mesenchymal transition signal to ETCs. In summary, these results suggest that poor-prognostic CCIs activated along with tumor grades can be potential therapeutic targets for PDAC.…”
Section: Resultssupporting
confidence: 58%
“…4 B and C). Given recent studies showing that CALR promotes epithelial-mesenchymal transition in PDAC [ 28 , 29 ], our results indicate that CALR and ITGA3 could be one of the pathways through which CAFs send the epithelial-mesenchymal transition signal to ETCs. In summary, these results suggest that poor-prognostic CCIs activated along with tumor grades can be potential therapeutic targets for PDAC.…”
Section: Resultssupporting
confidence: 58%
“…The TG used as an inducer of ERS has been reported in previous studies [23,42] Our results indicated that the putative IRES can effectively initiate the expression of GFP in vitro (Fig. 6).…”
Section: Discussionsupporting
confidence: 77%
“…PERK is also responsible for the constitutive activation of Nrf2 in EMT dedifferentiated breast epithelial cells, leading to the activation of a multidrug-resistant (MDR) mechanism and insensitivity to chemotherapy [ 180 ]. In pancreatic cancer cells, induction of acute ERS with thapsigargin activated PERK phosphorylation, accompanied by a decrease of EMT epithelial markers E-cadherin and ZO-1 and an increase of mesenchymal regulators Snail1, Slug, and ZEB1 [ 181 ].…”
Section: Relationship Between Ers and Emtmentioning
confidence: 99%